Hypothalamic Microglial Activation in Obesity: A Mini-Review - Mendes, Natália F.; Kim, Young-Bum; Velloso, Lício A.; Araújo, Eliana P. (Frontiers in Neuroscience, 2018)
Emerging data demonstrate that microglia activation plays a pivotal role in the development of hypothalamic inflammation in obesity. Early after the introduction of a high-fat diet, hypothalamic microglia undergo morphological and functional changes in response to excessive dietary saturated fats. Initially the resident microglia are affected; however, as diet-induced obesity persists, bone marrow-derived myeloid cells gradually replace resident microglia. Genetic and pharmacological approaches aimed at dampening the inflammatory activity in the hypothalamus of experimental models of obesity have proven beneficial to correct the obese phenotype and improve metabolic abnormalities commonly associated with obesity. This approach provides an experimental proof-of-concept that hypothalamic inflammation is central to the pathophysiology of obesity; understanding the details of the roles played by microglia in this process may help the development of preventive and therapeutic advances in the field. In this review, we discuss the potential mechanisms underlying hypothalamic microglial activation in high-fat induced obesity.